All Days 1993
DOI: 10.2118/26453-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cernent Resistivity and Implications for Measurement of Formation Resistivity Through Casing

Abstract: Measurement of formation resistivity through casing is an emerging logging technology, with prototype logging tools currently under development. Modeling studies show that the presence of cement could reduce the sensitivity of the TCRT [TM] (Through Casing Resistivity Tool [TM]). Physically this tool has some similarity to a laterolog. Measurements would be seriously affected if the cement was much more resistive than the formation. We have carried out a laboratory study of cement resistivity with the funding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Because no other cement information was available at the time of the data processing, the cement correction was performed using as the cement thickness half the difference between the bit size and casing size and using as the cement resistivity 5 Ohm-m, the average value from a laboratory cement study. 28 We conclude that the cement effect is usually small and can be removed.…”
Section: Field Log Examplesmentioning
confidence: 71%
See 1 more Smart Citation
“…Because no other cement information was available at the time of the data processing, the cement correction was performed using as the cement thickness half the difference between the bit size and casing size and using as the cement resistivity 5 Ohm-m, the average value from a laboratory cement study. 28 We conclude that the cement effect is usually small and can be removed.…”
Section: Field Log Examplesmentioning
confidence: 71%
“…[22][23][24][25][26][27][28] From an historical perspective, there is an additional major point to stress. When the first measurement techniques were proposed, there was considerable concern that the voltage measurements inside the casing would not necessarily be representative of quantities directly related to the formation resistivity.…”
Section: Tcr Technology Developmentmentioning
confidence: 99%
“…Since no in-situ R Cmt measurement can be made today, assumptions must be made on cement resistivity. Klein (1993) studied the cement electrical properties in the laboratory and showed that its resistivity is in the range of 1 to 10 ohmm.…”
Section: Effect Of Original-hole Conditions and Cementmentioning
confidence: 99%